(untitled) (World Science, 2021)
The rate of infertility in married couples of reproductive age in this country makes up from 10 to 15%, in some regions this value is close to 20% - a critical level that has a negative impact on demographic figures. The rate of pregnancy depends directly on the women’s age and decreases by 3.3 times starting from the age of 19 and by the age of 48. The decrease in the ability to conceive is accounted for by subtle mechanisms related to the deterioration of the quality of oocytes. The patients who are prepared for an extracorporeal fertilization program (ECF) and do not respond to controlled ovarian hyperstimulation protocols are considered to be poor respondents. Many studies focused on the development of an optimal treatment method. However, none of the approaches seems to be effective enough to guarantee a successful use. Platelet-rich plasma is a new and promising method that is successfully used in the reproductive science to solve a number of medical problems. All the patients whose common features were low oocyte output and poor embryo quality as well as failed ECF attempts were offered a treatment method of autologous PRP therapy after their written consent. Three months later, one obtained astonishing results, which by the markers of biochemical infertility alone could be classified as a complete biological phenomenon and are also characterized by improved embryo quality. The results of hormonal homeostasis show a decrease in the level of the follicle-stimulating hormone by 67.33% while the level of the anti-muellerian hormone is 75.18% higher. Thus, the use of the PRP therapy in poor respondents helps them to overcome their problematic reproductive barrier.